WebGIS Design at the Department of Agriculture and Plantations of Batu Bara Regency - Naibaho, Frainskoy Rio (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2025)
The development of technology today has grown very rapidly, this is marked by the birth of remote sensing technology. In order to maximize data visualization services, the Batu Bara district agriculture and plantation office has successfully implemented the WebGIS application. The data displayed on the WebGIS is data on agricultural tools and machinery, district boundaries, irrigation boundaries, rice field boundaries, farm roads, and district roads. All data can be displayed well on Google Maps-based WebGIS. The data is displayed based on the coordinate points in the database. There are 5 stages in this study, namely, literature study, data collection, data normalization and analysis, visualization, and implementation. The data can be accessed publicly, as a service to the community so that the community can find out and get more transparent information. This is one of the innovations of the Batu Bara district agriculture and plantation office.